Nanoparticulate Copper(II) Oxide Catalyzed Synthesis of Guanidine Derivatives and Their Conversion into Functionalized Iminoguanidines - Yavari, Issa; Sodagar, Esmat; Nematpour, Manijeh; Askarian-Amiri, Mohammad (Synlett, 2015)
A simple synthesis of functionalized iminoguanidines from N-sulfoketenimines and N,N′,N′′-trisubstituted guanidines, generated by nanoparticulate copper(II) oxide-catalyzed hydroamination of di(cyclo)alkylcarbodiimides, is described.
Keywords: imines; guanidines; ketenes; tandem reactions; azides; alkynes; carbodiimides